Instructional technology: A must in teacher education - Look Loy, Victor
This article examines: 1) some of the software or intellectual aspects of educational technology, that is, the aspects that apply learning principles, and teaching strategies and techniques to the process of education; and 2) the hardware component that mechanizes the learning process by the use of projectors, teaching machines, language laboratories, radio, television, and the computer. It is suggested that the ineffective teaching practices of the past need not be a characteristic of today's teacher if the potential inherent in the hardware and software of the technology is skilfully utilized. The implications for the design of teacher education programmes are mentioned
Keywords: Educational technology